EPIGENETIC REGULATION OF ESTROGEN GENE EXPRESSION IN OVARY CANCER IN HUMAN - Salih, Alyaa Abdulhadi (Journal of Medical Genetics and Clinical Biology, 2024)
Objective: This study examines how epigenetic mechanisms control the expression of the estrogen receptor (ER) gene in ovarian cancer, concentrating on DNA methylation, histone modifications, and non-coding RNAs in Iraqi population samples. Method: Bisulfite sequencing was used to measure the DNA methylation levels of the ER gene in tissue samples from ovarian cancer patients and healthy controls, and chromatin immunoprecipitation (ChIP) tests were used to examine histone alterations. Using RNA sequencing, important non-coding RNAs affecting ER pathways were found. The epigenetic variations between malignant and healthy tissues were assessed using comparative analysis. Results: The results showed that the ER gene was significantly more methylated in cancer tissues (67%) than in healthy samples (21%), which resulted in decreased cellular estrogen responses and increased proliferation. Oncogenes were activated by elevated histone H3K9 acetylation levels (1.7 AU vs. 0.8 AU), but tumor suppressor genes were inhibited by elevated H3K27 methylation (2.1 AU). These modifications draw attention to important epigenetic modifications that aid in the development of ovarian cancer. Novelty: By identifying region-specific epigenetic markers in ovarian cancer, this work highlights the significance of population-targeted research in enhancing cancer outcomes and provides insights into tailored therapy approaches.